Transformation of Education Quality in Islamic Higher Education Institutions through Organizational Culture and Integrated Quality Management - Hasbi, Muh.; Alim, Nur; Machmud, Hadi (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
This study found that a strong organizational culture at IAIN Sultan Amai Gorontalo plays a crucial role in enhancing the quality of education. Values such as discipline, commitment to quality, and collaboration among the academic community form behavior patterns that support the achievement of institutional goals. The implementation of integrated quality management also significantly contributes through a system that involves planning, control, and systematic evaluation. Integrated quality management at IAIN Sultan Amai Gorontalo involves all related parties, from leadership to educators and educational staff. The process of periodic performance measurement, combined with the use of information technology in evaluations, enhances the quality of teaching and learning. As a result, there has been a significant increase in both academic and non-academic aspects. This study demonstrates that a robust organizational culture and integrated quality management can enhance the quality of education. Islamic higher education institutions are expected to develop organizational culture values that support educational quality, such as collaboration and shared commitment. Additionally, regular performance evaluations are necessary for continuous improvement and effective policy-making to enhance academic quality. This research can also serve as a reference in the development of educational policies in Indonesia.